Atlas of Human Anatomy / Frank H. Netter - Netter, Frank H
MD's Atlas of Human Anatomy offers unsurpassed depictions of the human body in clear, brilliant detail - all from a clinician's perspective. With its emphasis on anatomic relationships and clinically relevant views, Dr. Netter's work provides a coherent, lasting visual vocabulary for understanding anatomy and how it applies to medicine today.